2017
DOI: 10.1007/s12185-017-2198-0
|View full text |Cite
|
Sign up to set email alerts
|

Clofarabine-based chemotherapy as a bridge to transplant in the setting of refractory or relapsed acute myeloid leukemia, after at least one previous unsuccessful salvage treatment containing fludarabine: a single institution experience

Abstract: For refractory or relapsed acute myeloid leukemia patients, allogeneic hematopoietic stem cell transplantation is the only curative treatment option, but the disease must be in remission before this can be attempted. "Salvage" therapy regimens containing high-dose cytarabine plus fludarabine or cladribine with or without anthracyclines or plus mitoxantrone and etoposide fail in 30-50% of cases. We report the outcome of 14 patients treated with a clofarabine-based treatment administered after at least one faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Of note, the allo-HSCT rate in patients receiving salvage chemotherapy in this study was 11%, compared with 15% in patients receiving gilteritinib in the phase 3 ADMIRAL trial [6] and 20% in a phase 2 study of the FLT3 inhibitor lestaurtinib [5] in patients with FLT3-ITD AML. In studies of FLT3-unselected populations, allo-HSCT rates with salvage chemotherapy are variable (% 15%-42%) and are often based on small sample sizes with heterogenous populations of patients with differD 3 4 4 X Xing cytogenetic and molecular features and risk factors [35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the allo-HSCT rate in patients receiving salvage chemotherapy in this study was 11%, compared with 15% in patients receiving gilteritinib in the phase 3 ADMIRAL trial [6] and 20% in a phase 2 study of the FLT3 inhibitor lestaurtinib [5] in patients with FLT3-ITD AML. In studies of FLT3-unselected populations, allo-HSCT rates with salvage chemotherapy are variable (% 15%-42%) and are often based on small sample sizes with heterogenous populations of patients with differD 3 4 4 X Xing cytogenetic and molecular features and risk factors [35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Clofarabine increases the anti-leukemic activity of cytarabine, 9 and recent studies have provided evidence in support of its effectiveness against both adult and pediatric AML. 10 12 , 21 , 22 Accordingly, Rubnitz et al 23 suggested that clofarabine could be used instead of anthracycline and etoposide during remission therapy for childhood AML, while Molteni et al 11 showed the potential of clofarabine-based chemotherapy as a bridge toward transplantation in patients with refractory/relapsed AML, especially after fludarabine-based salvage chemotherapy has been attempted.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Studies have shown that clofarabine is effective against pediatric acute leukemia, 7,8 and that its combination with cytarabine was effective against AML. [9][10][11][12] Moreover, a few studies have indicated that combination chemotherapy involving clofarabine, cyclophosphamide, and etoposide was effective against relapsed/refractory acute lymphocytic leukemia (ALL) and AML. [13][14][15][16] However, the enrolled cases primarily involved ALL, due to the low number of registered AML cases.…”
Section: Introductionmentioning
confidence: 99%
“…The sequential treatment with chemotherapy and reduced-intensity conditioning for allo-HSCT has shown a potential benefit in relapsed and refractory patients [7,8], where the induction chemotherapy was given just before conditioning and patients received allo-HSCT at nadir. More recently, clofarabine has been used for preconditioning [9][10][11][12][13]. However, clofarabine is less frequently used in haploidentical and mismatched transplants.…”
Section: Introductionmentioning
confidence: 99%